Profit Sharing Agreement Between Eti Country and Petuanan Area In the context of Capacity Building - Sopamena, Ronald Fadly (Law Research Review Quarterly, 2022)
In Eti Village, which is located in the West Seram sub-district, West Seram Regency, there is still an agreement for marine and plantation products sharing between the Petuanan Region and the State Government of Eti Village as the parent country in the context of capacity building. This Profit Sharing Agreement is known as the ngase system and has been implemented from 1979 to 2021This study aims to identify and analyze the profit sharing agreement from the Petuanan Area to the Parent State in the context of capacity building, and also the legal consequences of the revenue sharing agreement from the Petuanan Area to the Parent State in the context of capacity building. In accordance with the problems and objectives of this research, the type of research used is sociolegal research, namely a combination research method between doctrinal law research methods and empirical legal research methods. Based on the author's study, the ngase system is a profit-sharing agreement in oral form which is applied in the Eti Country and applies as an agreement so that it has binding legal consequences.